PWM Control of a DC Motor Used to Drive a Conveyor Belt. (2015) - Petru, Livinti; Mazen, Ghandour
Abstract: This work presents an experimental stand for the PWM control of a DC motor used for driving a conveyor belt. For supplying the DC motor an H-bridge has been used that allows the reversal of the motor rotation wise. The PWM signal is generated by an ARDUINO UNO board, equipped with an Atmega 328 microcontroller. For controlling the ARDUINO UNO board, a program has been issued in the LabVIEW 2013 programming environment. The purpose of the experimental stand consists of studying the running characteristics of the conveyor belts under laboratory conditions, so that, further on, such driving systems can be implemented to industrial applications as well. Unlike other driving systems of conveyor belts, this system allows the optimization, by trials, of their running duties. The running duty of a conveyor belt may be modified by modifying the duty-cycle value of the PWM signals that controls the transistors of the H-bridge that supplies the DC motor. The PWM control of the DC motor provides the performances settled at the designing stage.